Collaborative Cooperation In Education Institution In Realizing Quality Culture Of Quality Human Resourch - Agus Prasetya; Ninik Srijani; Sulistyono Sulistyono (Syntax Corporation, 2022)
In 1984 President Soeharto planned the establishment of the Open University (abbreviated asUT), precisely on September 4 at the Merdeka Palace, in accordance with the mandate of the 1945 ConstitutionArticle 31 states that the government is obliged to provide facilities, infrastructure, opportunities, and citizensin order to educate the nation's life for the progress of the nation and state. Manycitizens who cannot get schools to seek knowledge for classical reasons, namely time, cost,limited number, not open, limited age, limited space and time, must leavework, boarding out of town, that's why UT is here to answer the challenge.The implementation of UT in the regions collaborates between Open Universities and DinasEducation, managers, tutors and students, is a necessity that cannotavoided. This research is a qualitative research that is descriptive data throughnarrative, story, words to the subject under study, while the social paradigm isSocial definition because it examines human beings and their social interactions, in a micro society.While the type of research is a case study because it has specificity, interesting, settingtypical, people's attention involves various institutions. Data Analysis withusing the Interactive model of Miles and Huberman which includes the Collection Data stage,Data Reduction, Data Display, and Conclusion Data. To explore data, usethe study of the theory of Sociology, namely Strukturasi Anthony Giddens, is a theory that focuseson structures and agents in social practice, on the one hand helping humans to fulfilltheir revised needs include the institution on the other hand he presents ainstitutional collaboration. The aim of the research is to understand the collaboration between institutionsin the program organizer, UT-UPBJJ can increase numbersquantitative and qualitative student participation, as well as national dissemination of UT.